Edmodo Sebagai Media Alternatif Pada Pembelajaran Daring Di Sekolah Dasar Selama Masa Pandemi - Bayu Fitra Prisuna (UIR Press, 2022)
This research is a literature study with a qualitative approach that aims to describe the role of Edmodo as an alternative media for online learning in elementary schools during the pandemic. In this study, the author uses various written sources from scientific articles originating from national and international journals as well as documents that are considered relevant to the study in this research. The results of the study show that Edmodo has a role as an online learning media that can be seen from the features it contains, including: note (notes), assignment (tasks), poll (election), quiz (quiz), library (library). Thus Edmodo is one of the effective alternative media to be used in online learning in elementary schools during the pandemic. One of the obstacles faced by elementary school students in using Edmodo as an alternative online learning media during the pandemic is the tendency for one-way learning and the lack of interaction between students and teachers and between fellow students, which results in learning not going as expected.